Identification of Contaminant Fungi for Cocoa Seeds (Theobroma cacao L.) During Storage in the Exporter's Warehouse, Sorong City, Southwest Papua - Ohorella, Zainuddin; A. A. Gafur, Muzna.; Paparang, Ria Resti (Agrikan Jurnal Agribisnis Perikanan, 2023)
The low quality of cocoa beans because they do not meet SNI standards can cause losses for exporters because they are subject to automatic discounting as a result of the product being detained (automatic detention). This problem can affect the competitiveness of Indonesian cocoa in international market trade. Anticipation of the low quality of export cocoa beans really needs to be done to minimize the level of damage to cocoa beans due to contaminant fungal attacks. The types of contaminant fungi that attack cocoa beans are from the genera Aspergillus, Penicillium, Fusarium, Rhizopus and Mucor. The research was conducted from June to August 2022 at the Sorong City Plant Quarantine Laboratory. The study used a qualitative method and took a sample of 0.5 kg of cocoa beans from the top, middle and bottom of the storage sacks in the exporter's warehouse, using a purposive sampling method. The results of the study found 7 types of contaminant fungi and 4 species from the Ascomycetes class which mostly attacked cocoa beans, namely Aspergillus flavus, Aspergillus fumigatus, Aspergillus clavatus and Penicillium sp.